A Camp on Cat Lake: Rocky Mountains of Colorado - Judi Bauer (Oz, 1985)
Lower Cataract Lake is set in the Rocky Mountains of Colorado under the auspices of the 14,000 foot peak of Eagle's Nest Mountain. The northern slopes are densely populated with a variety of pine while the southern slopes, where the camp is located, are covered with stands of aspen and bluegrass meadows...